Local stories and national history of China II - Chunsheng, Chen author.
1 online resource (284 pages)
Keywords: This book is the second in a two-volume set examining the social history of the Hanjiang River region in southern China from the Song Dynasty to the modern era. It explores how clan structures, temple networks, and overseas Chinese communities shaped the region's development.The volume first analyzes the evolution of social power structures during the Qing Dynasty, showing how state systems influenced local development through clan organization and maritime trade networks. It then looks at how Shantou grew as an important city, and how Chinese charities, beliefs, and networks around the South China Sea grew too. The text documents the region's transformation into a distinctive "hometown" society, defined by its overseas connections and evolving cultural identities.This volume is an essential resource for scholars and students of pre-modern and modern Chinese social history, historical anthropology, China's modern trade networks, overseas communities, and diaspora studies.